Advanced Graphic Communications, Packaging Technology and Materials - Ouyang, Yun; Xu, Min; Yang, Li; Ouyang, Yujie (Lecture Notes in Electrical Engineering, 2016)
This book includes a selection of reviewed papers presented at the 2015, 4th China Academic Conference on Printing and Packaging, which was held on October 22-24, 2015 in Hangzhou, China. The conference was jointly organized by the China Academy of Printing Technology, Beijing Institute of Graphic Communication, and Hangzhou Dianzi University. With 3 keynote talks and 200 presented papers on graphic communications, packaging technologies and materials, the conference attracted more than 400 scientists.  These proceedings cover the recent research outcomes on color science and technology, image-processing technology, digital-media technology, printing-engineering technology, packaging-engineering technology etc. They will be of interest to university researchers, R&D engineers and graduate students in graphic communications, packaging, color science, image science, materials science, computer science, digital media and network technology fields.